Ai Superpowers : China, Silicon Valley, and the New World Order. - Lee, Kai-Fu.; ProQuest (firma) (: HarperCollins Publishers, 2018)
A New York Times Bestseller One of the world's most respected experts on AI and China reveals that China has suddenly caught up to the United States at an astonishingly rapid and unexpected pace.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: elektronické knihy; electronic books